Systematic reviews to support evidence-based medicine : how to review and apply findings of healthcare research /: how to review and apply findings of healthcare research. (2011) - Khan, Khalid Saeed; Kunz, Regina; Kleijnen, Jos; Antes, Gerd
No abstract available